2009
DOI: 10.1111/j.1936-4490.2005.tb00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Work Adjustment and Job Satisfaction of Filipino Immigrant Employees in Canada

Abstract: This study investigates the work adjustment and job satisfaction of Filipino immigrants in Canada to explore the impact of self‐efficacy and perceived social support from different sources, such as other immigrant coworkers, Canadian‐born coworkers and management. The sample is composed of 142 Filipino immigrant employees. The results show that Filipino immigrant employees' work adjustment is significantly correlated with self‐efficacy and perceived support from peer immigrants and Canadian‐borns, while job sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 63 publications
5
51
0
Order By: Relevance
“…In our study, participants highlighted the importance of access to resources and services that helped them to gain perspective, insight, motivation, and confidence. Similarly, adequate support and training have been found to be crucial to the adjustment of immigrants in the workforce (Wang & Jordache Sangalang, 2005). In our study, participants highlighted the necessity of a supportive work environment to help them to do well with change.…”
Section: Discussionmentioning
confidence: 83%
“…In our study, participants highlighted the importance of access to resources and services that helped them to gain perspective, insight, motivation, and confidence. Similarly, adequate support and training have been found to be crucial to the adjustment of immigrants in the workforce (Wang & Jordache Sangalang, 2005). In our study, participants highlighted the necessity of a supportive work environment to help them to do well with change.…”
Section: Discussionmentioning
confidence: 83%
“…According to Choi and Thomas (2009), social support can have a significant influence on the acculturation attitudes of immigrants. Wang and Sangalang (2005) point out that those immigrant employees who get more support from co-workers and management in the workplace adjust better to their working environment and are more likely to feel satisfied with their jobs. The reason for this relationship is that social support from these sources enables immigrant employees to better understand their jobs and get more information about the organization and therefore they more readily acculturate into the workplace and further improve their job performance.…”
Section: Perceived Mainstream Language Proficiencymentioning
confidence: 96%
“…Social support provided by co-cultural co-workers was however unrelated to acculturative stress. In Wang and Sangalang's (2005) study of Filipino immigrants, perceived support from Canadian-born (host national) co-workers correlated positively with job satisfaction, whereas support from peer immigrant co-workers was not related to job satisfaction. Two other studies, one conducted in Germany (Hoppe, 2011) and the other in the US (Hoppe, Heaney, & Fujishiro, 2010), also showed that social relations at work are particularly important for immigrants' well-being.…”
Section: Immigrants: the Specific Importance Of Host National Co-workmentioning
confidence: 74%
“…Two studies (Amason et al, 1999;Wang & Sangalang, 2005) are exceptions in this regard, as they take into account the source of support when looking at the social support − well-being link among immigrant employees. In the study by Amason et al (1999), social support received from host national (Anglo-Americans) co-workers was negatively related to the emotional acculturative stress of Hispanic immigrants.…”
Section: Immigrants: the Specific Importance Of Host National Co-workmentioning
confidence: 92%